2012
DOI: 10.4236/aid.2012.24017
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cholesterol Levels at the Onset of Bloodstream Infection Have Prognostic Value

Abstract: Objective: The aims of this study were to investigate the changes in serum cholesterol levels at the onset of bloodstream infection (BSI) and to determine whether serum cholesterol levels were associated with patients' clinical backgrounds and the prognosis of BSI. Methods: A retrospective chart review was done to collect demographic information and the subjects' medical history, invasive procedures, and medications. Patients and Methods: From April 2003 to March 2006, all patients aged ≥20 years with positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Chenaud et al [ 12 ] showed that decreasing serum apolipoprotein AI levels are correlated with increasing levels of sepsis markers, such as CRP, PCT, and interleukin-6. The critical cholesterol levels in these patients were 100–135 mg/dl, depending on the study [ 13 14 15 ]. In the present study, the threshold level of cholesterol was 100 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chenaud et al [ 12 ] showed that decreasing serum apolipoprotein AI levels are correlated with increasing levels of sepsis markers, such as CRP, PCT, and interleukin-6. The critical cholesterol levels in these patients were 100–135 mg/dl, depending on the study [ 13 14 15 ]. In the present study, the threshold level of cholesterol was 100 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…Biller et al [ 17 ] found that a cholesterol level > 80 mg/dl is associated with a survival AUC of 0.715 in patients with infection, with sensitivity of 72% and specificity of 66%. Kitazawa et al [ 15 ] reported that patients with a bloodstream infection and lower cholesterol levels tended to have higher 30 day mortality, with an AUC of 0.66, sensitivity of 100% and specificity of 39%.…”
Section: Discussionmentioning
confidence: 99%
“…15 Penelitian di Jepang, pada pasien dewasa dengan kultur darah positif didapatkan mortalitas lebih tinggi pada pasien dengan kadar kolesterol lebih rendah (nilai cut-off 143 mg/dL) dengan nilai p=0,04. 18 Demikian juga penelitian yang dilakukan pada pasien infeksi di Jerman, didapatkan angka mortalitas lebih tinggi (82%) pada kadar kolesterol ≤50 mg/dL dibandingkan kadar kolesterol ≥100 mg/dL (angka mortalitas hanya 21%). Namun pada penelitian kami tidak dilakukan penilaian hubungan profil lipid dan mortalitas pada pasien sepsis.…”
Section: Metodeunclassified
“…Namun demikian perubahan ini tidak bermakna secara klinis. 18 Kelebihan penelitian ini adalah nilai cut-off didapatkan berdasarkan kurva ROC dan penelitian ini menilai hubungan masing-masing komponen profil lipid dengan derajat keparahan penyakit. Kelemahan penelitian ini adalah pengambilan sampel tidak dilakukan secara berkala.…”
Section: Metodeunclassified